Multiparametric Magnetic Resonance Imaging Findings In Suspected Cerebral Venous Sinus Thrombosis: A Cross-Sectional Study At A Tertiary Care Hospital. - Kumar, Pasupuleti Santosh; Pandian, Soundara (Journal of Neonatal Surgery, 2025)
Background: Cerebral venous sinus thrombosis (CVST) is a rare but potentially fatal cerebrovascular disorder with a predilection for young women, particularly in the postpartum period. It presents with variable and non-specific clinical features, making MRI with magnetic resonance venography (MRV) the cornerstone of diagnosis. Susceptibility-weighted imaging (SWI) has emerged as an adjunctive sequence with superior sensitivity for cortical-vein thrombosis. This study characterises the MRI spectrum of CVST and evaluates the incremental diagnostic value of SWI. Methods: A cross-sectional study over 24 months included 120 consecutive adults with clinically suspected CVST undergoing 1.5/3-Tesla MRI brain with time-of-flight MRV (TOF-MRV), contrast-enhanced MRV (CE-MRV), diffusion-weighted imaging (DWI), FLAIR, and SWI. CVST was confirmed when a sinus filling defect or absent sinus flow was demonstrated on MRV with corroborating signal change on the sinus on conventional sequences. Results: CVST was confirmed in 78/120 (65.0%) suspected cases. Female:male ratio was 2.3:1; mean age 32.4 ± 11.6 years. Postpartum aetiology (28.2%) was most prevalent. The transverse sinus was most frequently involved (71.8%), often bilaterally (24.4%). Parenchymal haemorrhage was present in 35.9% and venous infarction in 41.0% of confirmed cases. SWI demonstrated superior sensitivity for cortical-vein thrombosis (88.2%) compared to TOF-MRV (55.9%). Conclusion: CVST was confirmed in 65% of clinically suspected cases. Postpartum state was the leading predisposing factor. SWI significantly improved cortical-vein thrombosis detection. A standardised multisequence MRI protocol including DWI, FLAIR, SWI, TOF-MRV, and CE-MRV is recommended for all suspected CVST cases..